Phage-Resistant Phase-Variant Sub-populations Mediate Herd Immunity Against Bacteriophage Invasion of Bacterial Meta-Populations - Turkington, Christopher J. R.; Morozov, Andrew; Clokie, Martha R. J.; Bayliss, Christopher D. (Frontiers in Microbiology, 2019)
Hypermutable loci are widespread in bacteria as mechanisms for rapid generation of phenotypic diversity within a population that enables survival of fluctuating, often antagonistic, selection pressures. Localized hypermutation can mediate phase variation and enable survival of bacteriophage predation due to high frequency, reversible alterations in the expression of phage receptors. As phase variation can also generate population-to-population heterogeneity, we hypothesized that this phenomenon may facilitate survival of spatially-separated bacterial populations from phage invasion in a manner analogous to herd immunity to infectious diseases in human populations. The lic2A gene of Haemophilus influenzae is subject to “ON” and “OFF” switches in expression mediated by mutations in a 5′CAAT repeat tract present within the reading frame. The enzyme encoded by lic2A mediates addition of a galactose moiety of the lipopolysaccharide. This moiety is required for attachment of the HP1C1 phage such that the ON state of the lic2A gene is associated with HP1c1 susceptibility while the OFF state is resistant to infection. We developed an “oscillating prey assay” to examine phage spread through a series of sub-populations of Haemophilus influenzae whose phage receptor is in an ON or OFF state. Phage extinction was frequently observed when the proportion of phage-resistant sub-populations exceeded 34%. In silico modeling indicated that phage extinction was interdependent on phage loss during transfer between sub-populations and the frequency of resistant sub-populations. In a fixed-area oscillating prey assay, heterogeneity in phage resistance was observed to generate vast differences in phage densities across a meta-population of multiple bacterial sub-populations resulting in protective quarantining of some sub-populations from phage attack. We conclude that phase-variable hypermutable loci produce bacterial “herd immunity” with resistant intermediary-populations acting as a barricade to reduce the viral load faced by phage-susceptible sub-populations. This paradigm of meta-population protection is applicable to evolution of hypermutable loci in multiple bacteria-phage and host-pathogen interactions.